2020
DOI: 10.21203/rs.3.rs-45710/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of COVID-19 Outbreak on Children’s Mental Health: A Comparative Study with Children Diagnosed and Isolated from Their Parents

Abstract: Background The current study aimed to compare the psychological responses of children exposed to different levels of stress during COVID-19 outbreak. Anxiety levels, negative thoughts, and quality of life of COVID-19 positive children (Child + group, n = 17), COVID-19 negative children who are isolated from their COVID-19 positive parent(s) (Parent + group, n = 59), and a control group (n = 64) were compared. Methods The participants completed a sociodemographic data form, the Screen for Child Anxiety and Re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To our knowledge, only one study has been done till now on COVID positive children/adolescents. 43 Future research should explore the longitudinal course of psychological symptoms, especially in connection to the changes in the prevailing situation (lockdown/relaxation in lockdown restrictions, home isolation/hospitalization, closure/re-opening of schools). Studies may also look at the help-seeking regarding the psychological symptoms associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has been done till now on COVID positive children/adolescents. 43 Future research should explore the longitudinal course of psychological symptoms, especially in connection to the changes in the prevailing situation (lockdown/relaxation in lockdown restrictions, home isolation/hospitalization, closure/re-opening of schools). Studies may also look at the help-seeking regarding the psychological symptoms associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…10 A study in Turkey showed that the mental health of children was negatively affected by separation from their parents during the COVID-19 pandemic. 11 In the light of this information, it is predicted that pandemic may have traumatic effects on children and their parents and this effect may increase the mutual traumatic impact between the child and the parent, besides traumatic effects on the parent and the child may be higher if the parent is a healthcare worker. It was thought that a high socioeconomic level of the family would reduce the traumatic impact, while a low socioeconomic level could increase the traumatic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Another study in China found the most commonly seen mental health symptoms in children and adolescents during the COVID-19 pandemic to be attention problems, behavioural disorders, irritability, and fears related to infection transmission [ 10 ]. A study in Turkey showed that the mental health of children was negatively affected by separation from their parents during the COVID-19 pandemic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%